2019
DOI: 10.1155/2019/6070685
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Performance Analysis of High‐Viscosity and Elastic Recovery Modified Asphalt Binder

Abstract: This study presented the preparation and performance of a kind of high viscosity and elastic recovery asphalt (HVERA) by using some modifiers. The performance of styrene-butadiene-styrene (SBS), rock asphalt (RA), crumb rubber (CR), and stabilizing agent (SA) for different modifiers was investigated by conventional binder test. Effects of modifiers on the high- and low-temperature properties of HVERA were investigated. The dynamic viscosity (DV) test, dynamic shear rheometer (DSR), and bending beam rheometer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…e higher its value, the better the high-temperature performance, deformation resistance, and cohesiveness of asphalt binders [9]. However, with the increase of dynamic viscosity at 60°C, the viscosity of HVA at 135°C is also higher than that of the ordinary modified asphalt binder [14]. ere is no doubt that this problem will increase the difficulty of construction, thus making asphalt mixtures harder to be produced and compacted for construction [15].…”
Section: Introductionmentioning
confidence: 99%
“…e higher its value, the better the high-temperature performance, deformation resistance, and cohesiveness of asphalt binders [9]. However, with the increase of dynamic viscosity at 60°C, the viscosity of HVA at 135°C is also higher than that of the ordinary modified asphalt binder [14]. ere is no doubt that this problem will increase the difficulty of construction, thus making asphalt mixtures harder to be produced and compacted for construction [15].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [10] added SBS, a plasticizer, and a cross-linking agent to an asphalt to prepare HVMA and studied the effects of the modifiers on the structure and rheological behavior of the SBS-modified asphalt through asphalt rheological test. Qu et al [13] prepared HVMA with modifiers such as SBS, rock pitch, and rubber powder; carried out a rotational viscosity test, DSR test, and BBR test; and found that the addition of modifiers can improve the high-and low-temperature properties of the asphalt and its mixture. Shi et al [14] used SBS/c9 petroleum resin blends (SPR) as a highviscosity asphalt modifier and compared it with the traditional modifier TPS; the results showed that the SPR modifier had good compatibility with asphalts in the production process, making SPR easier to disperse in asphalts with average particle size.…”
Section: Introductionmentioning
confidence: 99%
“…Asphalt 4.5.1. Micromorphology.e macroscopic properties of asphalt are closely related to its microstructure[31].e Complex shear modulus versus strain. Phase angle versus strain.…”
mentioning
confidence: 99%